Perancangan Animasi untuk Memperkenalkan Budaya Batak Toba bagi Generasi Muda - Evelyne Afriliana Gultom; Sultan Arif Rahmadianto; Didit Prasetyo Nugroho (Program Studi Desain Komunikasi Visual, Fakultas Sains dan Teknologi, Universitas Ma Chung, 2021)
Batak Toba is one of the Indonesian cultures that must be preserved. However, the Batak Toba culture has been forgotten by the younger generation, both Bataknese and non-Bataknese descendants. Many of the Batak Toba descendants, especially those who migrate, have left and forgotten their customs so that they do not know and cannot practice their own culture. Plus in this day and age many young Indonesians prefer foreign cultures rather than their own culture. Therefore, the right media to introduce Batak Toba culture is an animated video, because animation is popular and becoming a trend, as seen from the many animations that are popping up on social media today. In designing the introduction of Batak Toba culture, the method used is descriptive qualitative method. The data are obtained through literature studies, interviews and documentation. Animated video introduction of Batak Toba culture entitled